LATGALE IN THE POLISH PRESS AND EPISTOLOGRAPHY AT THE TURN OF THE 20TH CENTURY - Rembiszewska, Dorota Krystyna (Via Latgalica, 2017)
The article discusses the picture of Latgale presented in the following sources: articles and letters by Stefania Ulanowska, unpublished fragments of “Łotysze Inflant Polskich” (stored in the Archives of The Polish Academy of Sciences and in the Polish Academy of Learning in Krakow, No. 1–29a), letters found in the documents of Jan Karłowicz in Lithuanian State Historical Archives (fund. 1135, inv. 10), and articles (published in “Biblioteka Warszawska” in 1880 and in “Pamiętnik Fizjograficzny” in 1881) by Zygmunt Gloger, a 19th-century Polish ethnographer, who carried out research in the former territories of Livonia. In the letters and articles by S. Ulanowska, Latgale (the author does not use this name) is presented as a land of unlimited possibilities of ethnic and archaeological research. The author devotes much attention to the description of the region around Wielony (Viļāni) depicted in “Łotysze Inflant Polskich”. The articles by Zygmunt Gloger deal mainly with the 1880 excavations in Marienhaus (present Viļaka), which provide an opportunity to study and analyze customs, beliefs, and ethnic issues of the discussed region. The author mentions also the beliefs of Latvians from the area of Marienhaus and describes traditions related to bread baking in the Podlasie region.